A guide to the Choquard equation - Moroz, Vitaly; Van Schaftingen, Jean (Fixed point theory and algorithms for sciences and engineering, 2017)
We survey old and recent results dealing with the existence and properties of solutions to the Choquard type equations - Δ u + V ( x ) u = | x | - ( N - α ) ∗ | u | p | u | p - 2 u in R N , and some of its variants and extensions.